Fentanyl sublingual spray for breakthrough cancer pain in patients receiving transdermal fentanyl. (October 2016) - Alberts, David S; Smith, Christina Cognata; Parikh, Neha; Rauck, Richard L
Aim: To investigate the relationship between effective fentanyl sublingual spray (FSS) doses for breakthrough cancer pain (BTCP) and around-the-clock (ATC) transdermal fentanyl patch (TFP).Methods: Adults tolerating ATC opioids received open-label FSS for 26 days, followed by a 26-day double-blind phase for patients achieving an effective dose (100–1600 µg).Results: Out of 50 patients on ATC TFP at baseline, 32 (64%) achieved an effective dose. FSS effective dose moderately correlated with mean TFP dose (r = 0.4; p = 0.03). Patient satisfaction increased during the study. Common adverse event included nausea (9%) and peripheral edema (9%).Conclusion: FSS can be safely titrated to an effective dose for BTCP in patients receiving ATC TFP as chronic cancer pain medication.ClinicalTrials.gov identifier: NCT00538850